(untitled) (Journal of the College of Basic Education, 2022)
This chapter contains the introduction to the research and its importance. The administrative process and the advancement of administrative work in government institutions are discussed, thus considering that good management is the focus of every positive development within the institutions, in particular the faculties of physical education and sports sciences, and thus this development is reflected positively on the level of development of the country in all The fields as a result of this development and thus the management process is not like any other field and therefore it is an invisible force because it is intangible, but it can be proven by the results of its many efforts. Administrative efficiency, which facilitates the selection of the administrative leaders of the deanships of the faculties of physical education and sports sciences. The problem of the research lies in the absence of a measure of administrative efficiency for the deans of the faculties of physical education. As for the objectives of the research, it is to build and measure a measure of administrative efficiency and to identify the level of administrative efficiency and to identify the difference in efficiency. Administrative deans of faculties according to gender, and represent the current research community with members of the governing bodies Teaching for the faculties of physical education and sports sciences in Iraqi government universities, based on the data of the Ministry of Higher Education and Scientific Research / Statistics Department in Iraq for the year (2021), and their number is (1319) studying in (19) colleges, (1029) males and (290) females As for the sample of the current research, with a percentage of (45%) and in a proportional random stratified method, and from all faculties of physical education and sports sciences in Iraq, where the research sample reached (600) faculty members from the faculties of physical education and sports sciences, statistical methods were used to reach the results, which from The most important of which is the presence of a real difference between the arithmetic average for the field of administrative competence (personal, social, scientific and professional) for the dean, as well as the absence of a real (moral) difference in the level of competence of the dean as seen by the professors according to the gender of the professor (male, female), and the most important recommendations work to reconsider Assigning the position of dean of the college in accordance with the administrative efficiency and working on preparing administrative training programs for those who want to occupy the position of dean of the college from members of the faculty, holding seminars and lectures, holding conferences and scientific seminars on the rules and regulations of the university Administrative in the college.